2015
DOI: 10.1007/s00394-015-1115-7
|View full text |Cite
|
Sign up to set email alerts
|

Methylation patterns of Vegfb promoter are associated with gene and protein expression levels: the effects of dietary fatty acids

Abstract: According to our results, the regulation of Vegfb gene expression by dietary fatty acids may be mediated, at least in part, by epigenetic modifications on Vegfb promoter methylation. Considering the deep association between angiogenesis and tissue growth, we suggest the nutriepigenetic regulation of Vegfb as a key target in the control of the adipose tissue expansion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Moreover, Monastero et al analyzed the dietary FA-mediated epigenetic regulation induced by the Vascular Endothelial Growth Factor B (VEGF-B) in adipose tissue of rats and in 3 T3-L1 cell lines [50]. Rats fed with coconut oil presented higher levels of VEGF-B expression and levels of protein, which was associated with the methylation levels of the promoter.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Monastero et al analyzed the dietary FA-mediated epigenetic regulation induced by the Vascular Endothelial Growth Factor B (VEGF-B) in adipose tissue of rats and in 3 T3-L1 cell lines [50]. Rats fed with coconut oil presented higher levels of VEGF-B expression and levels of protein, which was associated with the methylation levels of the promoter.…”
Section: Resultsmentioning
confidence: 99%
“…Rats fed with coconut oil presented higher levels of VEGF-B expression and levels of protein, which was associated with the methylation levels of the promoter. Rats fed sunflower oil showed the lowest levels of VEGF-B while higher VEGF-B levels were associated with IR and T2D, as well as an impaired lipid metabolism [50].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of linoleic acid on angiogenesis modulation is contradictory, since both pro- and antiangiogenic roles have been described for this fatty acid in several models [167,168,169,170]. An interesting study showed that in vivo and in vitro treatments with linoleic acid produced an increase in the DNA methylation level of the VEGF-B promoter, which translated into lower levels of expression of the VEGF-B gene [171].…”
Section: Other Components Of the MD With Angiopreventive Potentialmentioning
confidence: 99%
“…VEGF-B is highly expressed in a number of metabolically active tissues and, consistent with its tissue distribution, has been shown to both modulate metabolic processes (e.g., fatty acid uptake and oxidation) and be regulated by the PPAR-␥ coactivator-1␣/ estrogen-related receptor-␣ axis (10,20). Nutrient levels have also been shown to influence epigenetic changes, which ultimately regulate the expression of VEGF-B; different dietary fatty acids have been shown to affect the methylation status of the VEGF-B promoter, influencing both mRNA and protein expression of VEGF-B (22). In addition, VEGF-B appears to exert a cardioprotective role, as evidenced by VEGF-B-induced preservation of cardiac function after a myocardial infarction (16).…”
mentioning
confidence: 99%